“The whisper of silent youth: memory and politics among young people during the 60s (Mar del Plata – Argentina) - Favero, Bettina (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This paper examines images and representations of the politics of Argentinian youth during the sixties in the XXth century, through oral interviews and publications of that period. The analyzed archive takes into account young people who were neither involved in a political party, nor did they participate in armed groups. After inishing school, this “other youth” went into the labor market and did not develop a college degree, traversing different cultural and political paths. In this way, an analysis of the social attitudes and political behavior of these subjects will be made, taking into account the political and institutional processes that characterized the decade of the sixties in Argentina.